Beneficial effects of time‐restricted feeding on gentamicin cytotoxicity in mouse cochlea and vestibular organs. Issue 2 (8th February 2022) - Gao, Ying; Kamogashira, Teru; Fujimoto, Chisato; Iwasaki, Shinichi; Yamasoba, Tatsuya
Abstract: Objective: Time restricted feeding (TRF), which is an intermittent fasting protocol, has been reported to decrease the toxicity and mortality rate associated with systemic gentamicin (GM) administration. The aim of this study is to evaluate the effect of TRF on GM‐induced vestibular and auditory function in mice. Methods: Japan Central Laboratory for Experimental Animals:Institute of Cancer Research (Jcl:ICR) mice were housed in a light–dark (LD) cycle (12:12) and were divided into three groups: (1) GM treatment at a dose of 220 mg/kg with TRF (feeding time: 8 h [9:00–17:00] during the light phase [7:00–19:00]) (GM + TRF group), (2) GM treatment at a dose of 220 mg/kg without TRF (GM group), and (3) saline injection with TRF (NS + TRF group). GM or saline was injected subcutaneously for 18 days (three courses of 5 days' injection + 2 days' rest, and an additional 3 days' injection). The auditory brainstem response (ABR) and vestibular evoked potential (VsEP) were tested after the treatments. The number of sensory hair cells in the cochlear organs and the vestibular organs were quantified using microscopic images. Results: All animals survived until the end of the experiment. One day after the last injection, GM + TRF mice showed significantly lower ABR thresholds at 4 kHz compared to GM mice, and there was no significant difference between the GM + TRF and NS + TRF groups. There was a significant difference of VsEP between GM and GM + TRF mice only in symmetric parabolic waves with linear acceleration and ramps waveform stimulation. GM + TRF mice showed significantly less outer and inner hair cell loss compared to GM mice. GM + TRF mice showed significantly less type II hair cell loss in the utricle and the ampulla compared to GM mice. Conclusion: TRF with daytime feeding reduced GM cytotoxicity in the cochlea and vestibular organs of ICR mice. Level of Evidence: NA Abstract : Time restricted feeding (TRF), which is an intermittent fasting protocol, has been reported to decrease the toxicity and mortality rate associated with systemic gentamicin (GM) administration. TRF with daytime feeding reduced GM cytotoxicity in the cochlea and vestibular organs of ICR mice. TRF can be a pivotal treatment for protecting cochlea hair cells and, to a lesser extent, vestibular hair cells, from GM‐induced damage.